Robust noise feature extraction for efficient classification - Dwivedi, Rupalee; Singh, Utkarsh; Gupta, Vaibhav (Journal of Advanced Research in Signal Processing and Applications, 2021)
In current paper, authors try to investigate regarding robust noise parameter to be used for efficient noise classification in noise parameter analysis which will then be used for intelligent volume control. One hundred and twenty original noises from environment were recorded with the help of a microphone connected to personal computer and stored as a noise samples in the computer’s memory. We have used MATLAB software for the software implementation of noise parameter analysis. Built-in programs have been used for Linear predictive coding (LPC) and Real cepstral parameter (RCEP) whereas user defined program was written for Mel Frequency Cepstral coefficient (MFCC) to get variation in noise parameters which may be further used for analysing the noise samples and classified through any one of the soft computing techniques viz. neural networks, fuzzy logic, genetic algorithms or a combination of these.  Forty samples each of three commonly encountered environmental noises (car, market and train) i.e., 120 noises in total have been considered in our study for estimation of three coefficients viz. Mel Frequency Cepstral coefficient, Linear predictive coding and real cepstral parameter. Our experimental results show that Mel Frequency Cepstral Frequencies are robust features for finding out variation in noise parameter estimates. How to cite this article: Mishra BP, Dwivedi R, Singh U et al. Robust Noise Feature Extraction for Efficient Classification. J Adv Res Sig Proc Appl 2021; 3(2): 1-5.